Peer Versus Pure Benchmarks in the Compensation of Mutual Fund Managers - Evans, Richard; Gómez, Juan-Pedro; Ma, Linlin; Tang, Yuehua (Journal of Financial and Quantitative Analysis, 2024)
Abstract We examine the role of peer (e.g., Lipper manager indices) versus pure (e.g., S&P 500) benchmarks in fund manager compensation. We model their impact on manager incentives and then test those predictions using novel data. We find that 71% of managers are compensated based on peer benchmarks. Consistent with the model, peer-benchmarked fund managers exhibit higher effort generating higher gross performance and collect higher fee income. Analyzing advisors’ choice between benchmark types, we show that peer-benchmarking advisors cater to more sophisticated and performance-sensitive investors, and are more likely to sell through direct channels, consistent with investor heterogeneity and market segmentation.